2019
DOI: 10.1249/mss.0000000000002003
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Induces Antiatherogenic Effects on Metabolomic Pathways

Abstract: Introduction: Arising evidence suggests that resistance training has the potential to induce beneficial modulation of biomarker profile. To date, however, only immediate responses to resistance training have been investigated using high-throughput metabolomics whereas the effects of chronic resistance training on biomarker profile have not been studied in detail. Methods: A total of 86 recreationally active healthy men without previous systematic resistance training background were allocated into i) a resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…Recently, Nikolova-Karakashian and Reid (2011) explained the 'sphingolipid rheostat' mechanism whereby sphingosine-1-phosphate slows fatigue, preserving force over time, ceramides, on the other hand, promote fatigue. The findings of Shepherd et al (2014) and Sarin et al (2019) were contradictory to the present study as they demonstrated that ST led to a significant increment in intramuscular triglyceride (IMTG) storage, muscle strength, and body fat percentage reduction. Shepherd et al (2014) assumed that greater IMTG storage might be created, leading to low availability of circulating ceramides following the ST.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, Nikolova-Karakashian and Reid (2011) explained the 'sphingolipid rheostat' mechanism whereby sphingosine-1-phosphate slows fatigue, preserving force over time, ceramides, on the other hand, promote fatigue. The findings of Shepherd et al (2014) and Sarin et al (2019) were contradictory to the present study as they demonstrated that ST led to a significant increment in intramuscular triglyceride (IMTG) storage, muscle strength, and body fat percentage reduction. Shepherd et al (2014) assumed that greater IMTG storage might be created, leading to low availability of circulating ceramides following the ST.…”
Section: Discussioncontrasting
confidence: 99%
“…Lowering blood cholesterol levels in athletes of group B in response to high intensity training load (Ra = 0.72) confirm the results of studies concerning strength training ( Costa et al, 2019 ; Sarin et al, 2019 ). However, these studies were not focused on the parameters of the volume and intensity of strength training, but only assessed the overall impact on training with weights on certain biochemical markers of blood.…”
Section: Discussionsupporting
confidence: 80%
“…One of the directions of this problem is related to the need to identify the most informative criteria for assessing the adaptive body changes in MMA athletes of strike fighting style and to find effective regimes of power training in the process of special training. Despite the generally accepted system of performance control in world practice, mainly by assessing the dynamics of morphometric parameters, changes in maximum muscle strength parameters (1RM) and special training ( Del Vecchio & Franchini, 2011 ; Schoenfeld et al, 2016 ; James et al, 2016a ; James et al, 2016b ; Loturco et al, 2021 ), in recent years scientists ( Marques et al, 2017 ; Walker et al, 2017 ; Crewther, Obmiński & Cook, 2018 ; Stajer, Vranes & Ostojic, 2020 ; Sarin et al, 2019 ) have paid attention to the use of biochemical blood markers to determine the course of adaptive changes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also support the correlation between RC and DM from the side. A DM prevention cohort study ( 22 ) shows that the RC concentration in the pre diabetes group is significantly higher than that in the normal population. Additionally, in a single-center cohort study ( 29 ), it was found that elevated RC levels were independently linked to a higher risk of developing new DM ( HR : 2.44, 95% CI : 1.50–3.89).…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses underscore the beneficial effects of higher levels of exercise on various health markers, including fasting blood glucose, total cholesterol, and triglycerides, suggesting the potential role of PA in regulating blood lipid levels ( 12 , 13 , 21 ). Additionally, as a component of the exercise regimen, resistance training has been associated with a decrease in RC levels, highlighting the connection between specific types of PA and lipid metabolism ( 22 ). Building upon the relationship between PA, RC, and DM mentioned above, we speculate that RC may play a crucial role in the complex interplay between PA and DM.…”
Section: Introductionmentioning
confidence: 99%